Magnetic resonance morphometry of the lumbar spinal canal in Zenica - Doboj Canton in Bosnia and Herzegovina - Belma Jaganjac; Amina Džidić-Krivić; Hakija Bečulić; Armin Šljivo; Emir Begagić; Adis Šišić (Medicinski glasnik, 2023)
Aim: To investigate morphometric determinants of lumbar canal in patients treated in Cantonal Hospital Zenica, and their variation according to gender. Methods: Morphometry of lumbar spinal canal was assessed in 52 patients treated at the Department of Neurosurgery of Cantonal Hospital Zenica in the period between September 2022 and November 2022. Data were collected retrospectively: anteroposterior and transverse diameter of lumbar vertebrae and intervertebral discs, as well as anteroposterior diameter of the spinal canal. Results: Gender appeared to be an important morphometric determinant, since it significantly differed when it comes to lumbar vertebral anteroposterior and transverse diameter, being mostly larger in males. Conclusion: This study increases anatomical knowledge of the vertebras and spinal canal of the lumbar region. Therefore, the measured dimensions of the lumbar vertebrae and spinal canal could be used as a baseline point for evaluation of patients presenting with low back pain and potential spinal canal stenosis.
Keywords: morphometry; spine; spinal canal; Torg-Pavlov ratio